Let's call "F" the age of the father
"B" the age of the brother
and "Y" your age
so we can create the followig equations from each sentence:
"My father's age divided by 5 is equal to my brother's age divided by 3"
F / 5 = B / 3
"My brother is 3 years older than me."
B = Y + 3
"My father's age is 3 less than 2 times my age."
F = 2 Y - 3
So now we replace in the very first equation we wrote, F with " 2 Y - 3" as per what the last equation gave us. And also we replace B with "Y + 3" as per what the second equation gave us. Therefore we end up with the following equation (with one only variable "Y"):
(2 Y - 3) / 5 = (Y + 3) / 3
we multiply both sides by "15" in order to cancel out both denominators (3 and 5):
3 (2 Y - 3) = 5 (Y + 3)
use distributive property
6 Y - 9 = 5 Y + 15
subtract 5 Y from both sides
6 Y - 5 Y - 9 = 15
Y - 9 = 15
add 9 to both sides
Y = 15 + 9 = 24
so Y = 24, that means that father's age is:
F = 2 Y - 3 = 2 (24) - 3 = 48 - 3 = 45
So the father's age is 45 years old.